Spatial Analysis of Microbiological Contaminants Based on Sanitary Hygiene of Drinking Water Depots in Tangerang City in 2024 - Nadya Nurhikmah; Mika Vernicia Humairo; Hanung Nurany; Vivi Novianti; Nurnaningsih Herya Ulfah (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Potable water needs to satisfy quality criteria for microbiological, chemical, and physical. Consuming water that fails to comply with established quality standards can lead to illnesses, including diarrhea. In Tangerang City, based on environment-related disease counseling data from 2024, diarrhea had the highest number of cases. The study examined the influence of DAM sanitary hygiene on the microbiological quality of refilled potable water and to map the distribution of DAM in Tangerang City in 2024. Methods: The study employed a quantitative analytic observation with a cross-sectional method and a secondary data analysis (SDA) with a geographic information system (GIS). Independent variable in this study is the assessment results of the sanitary hygiene DAM and dependent variable is the microbiological quality laboratory test result. The sample consisted of 104 DAM across Tangerang City. Data analysis utilized the Chi-square and binary logistic regression tests. Spatial analysis for thematic map creation was performed using QGIS. Results and Discussion: The results showed that 72.1% of DAM met the sanitary hygiene requirements but 63.5% still had microbiological contaminants. Statistical test results showed that the sanitary hygiene of DAM had a significant partial effect on the microbiological quality of drinking water with a p-value=0.002 (p<0.05). Conclusion: The study concluded that the sanitary hygiene of DAM affects the microbiological quality of drinking water. Other variabels outside the assessment aspects also contribute, such as a contact time of UV light or disinfection equipment, maintenance of filters, and water source quality.